An econometric model of corporate failure in periods of financial and currency crises in Nigeria / Abdulkadir Abdulrashid Rafindadi - Rafindadi, Abdulkadir Abdulrashid (2015)
Corporate organizations all over the world are the cradle and the propellers of economic growth and development. Unfortunately, however, the periods of financial and currency crises often pose significant threats to corporate survival through subsequent large impacts upon corporate value. The consensus in the majority of the literature surveyed reveals that misalignment of the exchange rate precedes currency crises. The literature further establishes that the periods of currency crisis, when addressed by harsh macroeconomic conditions, can plunge a country deep into financial crisis, and that the exposure of most firms to the exchange rate in that period is no longer linear. A number of questions, therefore, arise as a result of this. The first question is at what point, in terms of both the long-run and the short-run, during a period of financial and currency crises, could the degree of exchange rate misalignment influence the going concern value of a corporation. The second question deals with whether linear and non linear exchange rate exposures could pose a significant threat on the possibility for an entity to go bankrupt in Nigeria. The third question is, at what long-run and short-run effects could the Nigerian macroeconomic conditions influence corporate value towards bankruptcy in periods of financial and currency crises. The main objective of this study is to develop a model that can predict the possibility of corporate failure in periods of financial and currency crises in Nigeria. In order to achieve this, we analyzed the data of 102 companies consisting of indigenous and multinational entities from 19 sectors of the Nigerian economy over the period 1980 to 2011. The study employed the autoregressive distributed lag ARDL methodology in determining the effects of macroeconomic conditions on corporate values in Nigeria. The same methodology was also applied in determining the effect of linear exchange rate exposure on corporate value while in the nonlinear test the study applied the U test methodology. The findings from these investigations were used as an input to the mathematical empirics of the catastrophe theory with the aim of determining the catastrophic level by which these findings and the selected macroeconomic variables can impact upon the corporate values of the entities under survey, thus causing them to face the threat of bankruptcy. The result of this empirical exercise revealed that 30 local entities were in a state of bankruptcy because of the periods of currency and financial crises. While 7 cases from the multinational companies were discovered only in the period of financial crisis. These findings were also confirmed by the investigation using the artificial neural network on bankruptcy prediction. Following this development, the study proceeded to estimate the coefficient of those multinational companies that failed in the period of the financial crisis and the local companies that failed in each of the two periods. From these estimation results, the study was able to come up with the final model of corporate failure prediction in periods of financial and currency crisis for the case of Nigeria. The findings in this study were supported by a model fit and model accuracy level of 97% and 95% in the periods of financial and currency crises respectively. Overall, the findings in this study rejected the three null hypotheses proposed, thus paving the way for the acceptance of the three alternative hypotheses. Finally, the study proposed a research direction that will use panel data to cater for all sectors of the Nigerian economy, and possibly Africa and the globe at large.